Correction of idiopathic scoliosis using total transpedicular fixation in a patient with incomplete growth - Marija A. Chernyadjeva (Хирургия позвоночника, 2019)
The paper presents a completed case of the surgical treatment of a 10-year-old female patient with progressive grade IV idiopathic scoliosis who underwent surgical correction using total transpedicular fixation. The paper demonstrates long-term results of treatment of idiopathic scoliosis in the actively growing patient without the use of epiphyseodesis and staged surgical interventions.